Effectiveness of the Booster Dose in Protecting against COVID-19, Colombia 2022 (2023)
Vaccination has proven to be one of the most effective strategies against the COVID-19 pandemic. Several studies have evaluated and confirmed its effectiveness in different populations, particularly in reducing severe outcomes such as hospitalization and death. Some studies have investigated the effectiveness of vaccination against the infection, identifying the need for booster doses. This study aimed to explore the effectiveness of the vaccination schedule on the probability of infection in a sample of Colombian patients during the fourth wave of the COVID-19 pandemic, which was associated with the emergence and predominance of the Omicron variant. A cross-sectional study was conducted on individuals who underwent RT-PCR testing for COVID-19 detection in a dedicated laboratory in Bogotá, Colombia, between 30 December 2021 and 7 February 2022. A total of 1468 subjects was included in the study, of whom 36.6% (n = 538) had a positive PCR test for COVID-19. The comparison between fully vaccinated individuals with a booster dose and those without the booster dose revealed a 28% reduction in the odds of infection (OR = 0.719 CI 0.531–0.971). Age (OR = 1.009 CI 1.001–1.018) and low economic status (OR = 1.812 CI 1.416–2.319) were associated with an increased risk of infection. These findings suggest the need for a booster vaccination in the general population to improve the prevention rates of SARS-CoV-2 infection and mitigate severe outcomes.